(untitled) (Homoeopathy for All, 2024)
Homoeopathy is recognized globally, with the World Health Organization (WHO) noting its widespread use as a form of Traditional Medicine (TM) in all continents. Despite its popularity, homoeopathy faces challenges in providing standardized education. To modernize education, a unified, evidence-based approach is needed, incorporating scientific research, interdisciplinary collaboration, and continuous professional development. The LMHI (Liga Medicorum Homoeopathica Internationalis), in collaboration with European and other global organizations, aims to create an internationally acceptable curriculum for homoeopathy. Standardizing education globally can enhance the quality of homoeopathic practice and contribute to WHO’s goals for traditional medicine. The homoeopathic community is encouraged to join LMHI to strengthen homoeopathy globally. Qualified and registered homoeopaths can now obtain membership online at www.lmhi. org .